2012
DOI: 10.1002/jmv.23238
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of hepatitis A virus in patients in the ahwaz region of Iran

Abstract: Hepatitis A virus (HAV) is one of the etiologic agents of acute viral hepatitis, an important public health problem worldwide. The aim of this study was to investigate the genetic diversity of HAV in Southwest Iran (Ahwaz). A total of 59 sera were collected from acutely ill patients with anti-HAV IgM antibodies during 2009 and 2010 were tested also by RT-PCR targeting the 5' NCR for molecular diagnosis and examined in the VP1-2A and VP3-VP1 regions for genotyping. Twelve (20%) patients were detected VP1-2A by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 15 publications
(18 reference statements)
1
7
0
Order By: Relevance
“…However, worldwide, in most regions, there is co-circulation of IA and IB strains but the predominant strain usually accounts for more than 95% of HAV strains. Based on the recorded data, in Turkey and Middle East, 95% of HAV strains belong to genotype I subtype B [9,10], whereas in Europe the predominant strain is genotype I subtype A [11]. In Greece, the available data are in accordance with the other European countries [12].…”
Section: Discussionmentioning
confidence: 97%
“…However, worldwide, in most regions, there is co-circulation of IA and IB strains but the predominant strain usually accounts for more than 95% of HAV strains. Based on the recorded data, in Turkey and Middle East, 95% of HAV strains belong to genotype I subtype B [9,10], whereas in Europe the predominant strain is genotype I subtype A [11]. In Greece, the available data are in accordance with the other European countries [12].…”
Section: Discussionmentioning
confidence: 97%
“…Thus, based on the evaluation of 5UTR and VP12-A and the complete sequence of the HAV isolated from different regions of the world, it was confirmed that the isolated HAV strain from Ahvaz was a genotype IB. Nejati et al reported that the circulation of HAV genotype 1B among children with acute hepatitis A was dominant in Ahvaz city, Iran (17). The molecular epidemiology of HAV is limited in Iran and it is required to be investigated in different parts of Iran.…”
Section: Discussionmentioning
confidence: 99%
“…The PCR products were analyzed by electrophoresis through 2% agarose gel. The predicted PCR product size for VP1-2A was 234 bp (17).…”
Section: Nested Polymerase Chain Reaction For Vpv1-2amentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, however, only two of the nine positive HAV samples (22.2%) were of the IA genotype and none were from genotype IIIA; the other seven HAV sequences belonged to genotype IB. Genotype IB has given rise to epidemics in Turkey, Spain, and Iran . One study reported detecting this genotype in 2.2% of clinical gastroenteritis patients in Korea during 2007–2008 .…”
Section: Discussionmentioning
confidence: 99%